Hyaluronic acid in wound dressings - Cortes, Hernán; Caballero-Florán, Isaac H.; Mendoza-Muñoz, Néstor; Córdova-Villanueva, Elva N.; Escutia-Guadarrama, Lidia; Figueroa-González, Gabriela; Reyes-Hernández, Octavio D.; González-Del Carmen, Manuel; Varela-Cardoso, Miguel; Magaña, Jonathan J.; Florán, Benjamín; Del Prado-Audelo, María L.; et al. (Cellular and Molecular Biology, 2020)
Human skin possesses an essential function in the maintenance of individuals' health. However, it may undergo a variety of lesions that produce wounds of distinct severity. In this respect, instantly after any skin wound, the process of tissue regeneration and repair initiates. Nevertheless, diverse factors can delay this process, including bacterial infections, nutritional status, age, hypoxia, chronic diseases, necrosis, and vascular and arterial diseases. Thus, wound dressings are frequently used to improve wound healing. Those wound dressings are fabricated with diverse materials, which confer them different properties. In this regard, hyaluronic acid is a natural polysaccharide widely distributed in extracellular matrices of mammal tissues, which possesses remarkable attributes in terms of biocompatibility, biodegradability, and low cost. Moreover, hyaluronic acid exhibits several beneficial effects on wound healing, such as the decrease of inflammatory processes, regulation of tissue remodeling, and enhancement of angiogenesis. Therefore, in recent years, there is growing attention in this polysaccharide for the design and manufacture of novel wound dressings, which have shown encouraging properties. Here, we describe the different approaches of hyaluronic acid for the production of wound dressings, encompassing hydrogels, films, scaffolds, foams, topical formulations, and nanoformulations, as well as its beneficial effects on wound healing. Finally, we discuss perspectives about the use of hyaluronic acid in wound dressings.